2020
DOI: 10.1002/med.21718
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the molecular pathogenesis and nucleic acid therapeutics for Parkinson's disease in the precision medicine era

Abstract: Parkinson's disease (PD) is one of the most common neurodegenerative disorders that manifest various motor and nonmotor symptoms. Although currently available therapies can alleviate some of the symptoms, the disease continues to progress, leading eventually to severe motor and cognitive decline and reduced life expectancy. The past two decades have witnessed rapid progress in our understanding of the molecular and genetic pathogenesis of the disease, paving the way for the development of new therapeutic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 277 publications
(446 reference statements)
0
22
0
1
Order By: Relevance
“…26 At the cellular level, the pathophysiology of PD overlaps with numerous molecular pathways associated with the management of misfolded proteins. 27 Gene involvement of α-synuclein (SNCA) and leucine-rich repeat kinase 2 (LRRK2) implicate the ubiquitin-proteasomal system and autophagy-lysosomal pathway, respectively. 28,29 Mitochondrial dysfunction ranges from impaired mitochondrial maintenance, defective mitophagy, calcium imbalance, oxidative stress, and neuroinflammation.…”
Section: Pathophysiologymentioning
confidence: 99%
“…26 At the cellular level, the pathophysiology of PD overlaps with numerous molecular pathways associated with the management of misfolded proteins. 27 Gene involvement of α-synuclein (SNCA) and leucine-rich repeat kinase 2 (LRRK2) implicate the ubiquitin-proteasomal system and autophagy-lysosomal pathway, respectively. 28,29 Mitochondrial dysfunction ranges from impaired mitochondrial maintenance, defective mitophagy, calcium imbalance, oxidative stress, and neuroinflammation.…”
Section: Pathophysiologymentioning
confidence: 99%
“…With a recent progress in precision medicine and gene therapy, an entirely different way to reduce the LRRK2 activity has emerged: reducing the amount of the produced protein by means of: a) modifying gene expression and splicing events or b) by actively degrading the already produced protein. To this end, several tools have been developed, which are mostly nucleic acid agents, such as: antisense oligonucleotides (ASOs), small interfering RNAs (siRNAs), short hairpin RNAs (shRNAs), microRNAs (miRNAs), splice-switching ASOs, and aptamers [8]. Next to those, a line of small molecules called proteolysis-targeting chimeras (PROTACs) is a very promising tool in neurodegenerative medicine [116].…”
Section: Downregulating Lrrk2 Protein Levelsmentioning
confidence: 99%
“…Epidemiological studies have shown that there is strong genetic correlation, with mutations in six genes being the major cause: snca (α-synuclein), lrrk2 (Leucine-rich repeat kinase 2), vps35 (Vacuolar protein sorting ortholog 35), prkn (Parkin), dj1 (DJ-1), and pink1 (PTEN-induced kinase 1) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease (PD) is a progressive neurodegenerative disorder (NDD) caused by the progressive and selective degeneration of dopaminergic neurons within the substantia nigra pars compacta (SNpc) as well as accumulation of Lewy bodies containing α‐synuclein in neocortex and brainstem 1‐3 . While the precise mechanisms underlying pathogenesis of PD are not yet fully understood, several molecular mechanisms comprising oxidative stress, abnormal protein aggregation, mitochondrial dysfunction and neuroinflammation have been found to be strongly implicated in its pathogenesis, leading to programmed cell death of neurons 3‐7 . 1‐methyl‐4‐phenylpyridinium (MPP+) is a complex I activity inhibitor extensively utilized to induce PD chemically due to its potential to create mitochondrial impairment followed by oxidative stress and apoptosis, all of which have close associations with PD pathogenesis 2 , 4…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 While the precise mechanisms underlying pathogenesis of PD are not yet fully understood, several molecular mechanisms comprising oxidative stress, abnormal protein aggregation, mitochondrial dysfunction and neuroinflammation have been found to be strongly implicated in its pathogenesis, leading to programmed cell death of neurons. 3 , 4 , 5 , 6 , 7 1‐methyl‐4‐phenylpyridinium (MPP+) is a complex I activity inhibitor extensively utilized to induce PD chemically due to its potential to create mitochondrial impairment followed by oxidative stress and apoptosis, all of which have close associations with PD pathogenesis. 2 , 4…”
Section: Introductionmentioning
confidence: 99%